The Essence of Participation Training: A Phenomenological Examination of Graduate Student Experiences - Marjorie E. Treff (Adult Education Research Conference, 2008)
Data collected through interviews with individuals who recently experienced a Participation Training Institute reveals the nature of the phenomenon as reflective practice, as improvisational theater, and as eductive process. Comparative case studies might reveal productive similarities and differences between Participation Training and other forms of group learning.
Keywords: group learning method; reflective practice